Diaphragm muscle parameters as a predictive tool for weaning critically ill patients from mechanical ventilation: a systematic review and meta-analysis study - Yashar Iran Pour; Afrooz Zandifar (PAGEPress Publications, 2024)
Diaphragmatic ultrasound, valued for its portability and safety, assesses both structural and functional aspects of the diaphragm. While some studies support its predictive value, others conflict. This meta-analysis aims to clarify diaphragmatic ultrasound's role in predicting successful liberation from mechanical ventilation in intensive care settings. A systematic search was performed on Web of Science, Scopus, and PubMed up to March, 2024. The search strategy included a combination of relevant medical subject heading (MeSH) terms and relevant keywords. We defined our eligibility criteria based on the PICO framework. Two authors performed the data extraction using a standardized sheet. The pooled mean difference was calculated using random effects model and Hedges' g along with SD estimation. R and RStudio were used for the statistical analysis and creating forest and funnel plots. The pooled mean difference was 7.25 (95% CI: 4.20, 10.21) for DE among the two groups. We found a statistically significant difference among the two groups indicating that those with successful weaning from intubation had higher means of DE compared to those with failed weaning attempt (p-value<0.01). The mean difference of DTF was also higher among those with successful weaning from intubation compared to those with failed weaning attempt with the pooled mean difference of 14.52 (95% CI: 10.51, 18.54, p-value<0.01). The mean difference of RSBI was lower among those with successful weaning from intubation compared to those with failed weaning attempt with the pooled mean difference of -28.86 (95% CI: -41.82, -15.91, p-value<0.01). Our results suggest that evaluating diaphragmatic excursion and thickening fraction can reliably anticipate successful liberation from mechanical ventilation. However, significant heterogeneity was present among the included studies. High-quality research, particularly randomized clinical trials, is required to further elucidate the role of diaphragmatic ultrasound in predicting weaning from mechanical ventilation.